Prospects of pekin duck rearing in coastal region of Bangladesh - M. K. Rahman (Journal of Agriculture, Food and Environment)
This study was conducted to evaluate the prospects of Pekinducks which is associated with socio-economic status of the duck farmers and to analyze cost-benefit of Pekin duck farming. This work was performed in Bhola sadar and Doulatkhan Upazilla of Bhola district during 3 months from October to December, 2019. For this purpose the information was collected by direct interview using a questionnaire from 30 duck farmers. For cost-benefit analysis 50 numbers of Day Old Chicks (Pekin breed) were given to each 30 selected farmers. During 3 months of research feed and technical supports were provided from Grameen Jano Unnayan Sangstha (GJUS). Growth and body weight was observed and recorded in every week. The results reveal that most (50%) of the family were medium (5-7) sized. The majority of the respondents (46%) belonged to over 40 years aged group, about 43% of the farmers are illiterate, 33% received primary education, 24% of the respondents had secondary level education and no one of the respondents had higher level of education. In case of occupation we found that67% of the respondents were housewives, rest 23% were businessman and 10% were service holders, and 80% of the farmers have no idea about duck diseases. In case of rearing, all (100%) of the farmers use semi-intensive method, most of the farmers (90%) usebetel nut tree made house, 90% of the farmers use Sawdust as litter. In case of cost-benefit analysis, average body weight of Pekin duck in day-old 7 days, 15 days, 30 days, 60 days and 90 days were 60.43±2.08, 113±2.65, 282.87±9.26, 743.5±26.48, 1885±34.56 and 2732.83±40.45gm respectivelyand average Pekin duck rearing cost was Tk. 16041.83±420.12, income was Tk. 29400.4±896.44, net profit was Taka 13358.57±1037.15. Some problems were identified for duck farming including low price of duck meat. Therefore, if the problems are addressed properly, the Pekin duck farming in coastal belt of Bangladesh could be more profitable business for the farmers.